Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Assessing the Effects of Physical Barriers and Hypoxia on Red Drum Movement Patterns to Develop More Effective Management Strategies - Steven M. Baker; Eric A. Reyier; Bonnie J. Ahr; Geoffrey S. Cook (Fishes, 2023)
Human modification of coastal ecosystems often creates barriers to fish movement. Passive acoustic telemetry was used to quantify movement patterns and habitat use of red drums (Sciaenops ocellatus) within and around a complex of coastal impoundments, and explored how the presence of artificial structures (i.e., bollards and culverts) and a hypoxia-related mortality event impacted fish movement. Results indicated bollards impede the movement of individuals with head widths greater than the mean distance between bollards (~16.0 cm). Red drum home range area and daily distance traveled were related to water dissolved oxygen concentrations; as oxygen levels decreased, fish habitat use area decreased initially. However, continued exposure to hypoxic conditions increased fish cumulative daily distance traveled. When exposed to anoxic waters, fish daily distance traveled and rate of movement were greatly reduced. These findings suggest prolonged exposure to low dissolved oxygen in combination with artificial structures can reduce movement of red drum, increase risk of mortality, and decrease habitat connectivity. Constructing and maintaining (sediment and biofouling removal) larger culvert openings and/or using wider bollard spacing would improve water circulation in impoundments, increase habitat connectivity, and facilitate movement of large sportfish inhabiting Florida’s coastal waters.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Seasonality of biological and physical systems as indicators of climatic variation and change - Jake F. Weltzin; Julio L. Betancourt; Benjamin I. Cook; Theresa M. Crimmins; Carolyn A. F. Enquist; Michael D. Gerst; John E. Gross; Geoffrey M. Henebry; Rebecca A. Hufft; Melissa A. Kenney; John S. Kimball; Bradley C. Reed; et al. (Climatic Change, 2020)

A little SNP of this, a little SNP of that: The discovery of 116 single nucleotide polymorphism markers to enable the rapid identification of individual Pacific walrus (Odobenus rosmarus divergens) - Geoffrey M. Cook; Daniel J. Prince; Sean M. O’Rourke; Timothy L. King; Michael R. Miller; Cara J. Lewis; Michael S. Eackles; Patrick R. Lemons; Suresh A. Sethi; Jeffrey B. Olsen; John K. Wenburg (Conservation Genetics Resources, 2020)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Evidence of climate‐driven ecosystem reorganization in the Gulf of Mexico - Mandy Karnauskas; Michael J. Schirripa; J. K. Craig; Geoffrey S. Cook; Christopher R. Kelble; Juan J. Agar; Bryan A. Black; David B. Enfield; David Lindo‐Atichati; Barbara A. Muhling; Kevin M. Purcell; Paul M. Richards; et al. (Global Change Biology, 2015)
The Gulf of Mexico is one of the most ecologically and economically valuable marine ecosystems in the world and is affected by a variety of natural and anthropogenic phenomena including climate, hurricanes, coastal development, agricultural runoff, oil spills, and fishing. These complex and interacting stressors, together with the highly dynamic nature of this ecosystem, present challenges for the effective management of its resources. We analyze a compilation of over 100 indicators representing physical, biological, and economic aspects of the Gulf of Mexico and find that an ecosystem‐wide reorganization occurred in the mid‐1990s. Further analysis of fishery landings composition data indicates a major shift in the late 1970s coincident with the advent of US national fisheries management policy, as well as significant shifts in the mid‐1960s and the mid‐1990s. These latter shifts are aligned temporally with changes in a major climate mode in the Atlantic Ocean: the Atlantic Multidecadal Oscillation ( AMO ). We provide an explanation for how the AMO may drive physical changes in the Gulf of Mexico, thus altering higher‐level ecosystem dynamics. The hypotheses presented here should provide focus for further targeted studies, particularly in regard to whether and how management should adjust to different climate regimes or states of nature. Our study highlights the challenges in understanding the effects of climatic drivers against a background of multiple anthropogenic pressures, particularly in a system where these forces interact in complex and nonlinear ways.

The number of days on which increment occurs is the primary determinant of annual ring width in Callitris intratropica - David M. Drew; Anna E. Richards; Garry D. Cook; Geoffrey M. Downes; Warwick Gill; Patrick J. Baker (Trees, 2014)

Marine Metapopulations - Celeste Benham; Alison M. Cawood; Geoffrey S. Cook; Ange Darnell; Peter C. Davison; Miriam C. Goldstein; Ayana Elizabeth Johnson; Talina Konotchick; Elisa M. Maldonado; Alexis L. Pasulka; Jennifer C. Prairie; Serena M. Moseman; et al. (Marine Ecology, 2008)

Purification of ribulose 1,5-bisphosphate carboxylase/oxygenase and of carboxysomes from Thiobacillus thyasiris the putative symbiont of Thyasira flexuosa (Montagu) - Tom Lanaras; Catherine M. Cook; Ann P. Wood; Don P. Kelly; Geoffrey A. Codd (Archives of Microbiology, 1991)